Flow Hydrogenation of 1,3,5-Trinitrobenzenes over Cu-Based Catalysts as an Efficient Approach for the Preparation of Phloroglucinol Derivatives - Nuzhdin, Alexey L.; Shchurova, Irina А.; Bukhtiyarova, Marina V.; Bulavchenko, Olga A.; Alekseyeva, Natalia A.; Sysolyatin, Sergey V.; Bukhtiyarova, Galina A. (Synthesis, 2022)
An environmentally friendly and safe synthesis of phloroglucinol and its derivatives through the flow hydrogenation of 1,3,5-trinitrobenzenes on heterogeneous copper catalysts is reported. It was found that hydrogenation of 1,3,5-trinitrobenzene, 2,4,6-trinitrotoluene, 2,4,6-trinitroxylene, and 2,4,6-trinitromesitylene in methanol over Cu–Al mixed oxides derived from layered double hydroxides led to selective formation of the corresponding triaminobenzenes, which were isolated from the reaction mixture in the form of double salts with sulfuric acid and were stable in storage. Subsequent hydrolysis in aqueous solution gave the phloroglucinol derivatives in good yields (75–82%).
Keywords: trinitrobenzenes; hydrogenation; flow reactor; heterogeneous catalysis; mixed oxides; layered double hydroxides; phloroglucinol derivatives